Ultrasound Imaging in Reproductive Medicine Advances in Infertility Work-up, Treatment, and ART - Stadtmauer, Laurel; Tur-Kaspa, Ilan.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Can physicians, nurses, and ultrasonographers imagine infertility diagnosis and treatment and assisted reproductive technologies (ART) today without ultrasound? Ultrasound Imaging in Reproductive Medicine provides the most comprehensive know-how of modern imaging for all who are actively involved in ART and reproductive medicine. All that you wanted to know about the role of ultrasound - from the first time a woman comes to your clinic because of infertility to when she will conceive - is discussed in this book. With a critical evaluation of its advantages, Ultrasound Imaging in Reproductive Medicine covers traditional and emerging imaging technologies, including three-dimensional (3D) ultrasound for evaluating ovarian reserve, uterine cavity and tubal patency assessment, and ovarian and endometrial response for treatment. 3D ultrasound to assess ovarian and endometrial volume and 3D automated monitoring of follicles are covered in detail with up-to-date references. Imaging techniques of the embryo and embryo transfer, pulsed color Doppler techniques, and MRI-guided ultrasound procedures for treatment of uterine fibroids are also presented. See better, do ART better.
Part I: Ultrasound Technique -- Ultrasound in Reproductive Medicine: Is It Safe?- Principles of 3D Ultrasound -- Two Dimensional and Three Dimensional Doppler in Reproductive Medicine -- Legal Aspects of Ultrasound Imaging in Reproductive Medicine -- Part II: Ultrasound in Infertility Workup -- The Normal Ovary -- Ovarian Reserve and Ovarian Cysts -- Ultrasound and PCOS -- The Normal Uterus -- Congenital Uterine Anomalies -- Uterine Fibroids -- Endometrial Polyps -- Intrauterine Adhesions -- Sonohysterography (SHG) in Reproductive Medicine -- Evaluation of Tubal Patency (HyCoSy, Doppler) -- Hydrosalpinx -- Virtual Hysterosalpingography: A New Diagnostic Technique for the Study of the Female Reproductive Tract -- Ultrasound in Male Infertility -- Part III: Ultrasound in Infertility Treatment -- Ultrasound in Follicle Monitoring for Ovulation Induction/IUI -- 2D Ultrasound in Follicle Monitoring for ART -- 3D Ultrasound in Follicle Monitoring for ART -- Ultrasound Guided Surgical Procedures -- Ultrasound Role in Embryo Transfers -- Ultrasound and Ovarian Hyperstimulation Syndrome -- Pregnancy of Unknown Viability -- Ultrasound Evaluation of Ectopic Pregnancy -- Focused Ultrasound for Treatment of Fibroids.
Keywords: Reproductive medicine; Radiology; Reproductive Medicine; Imaging / Radiology; Diagnostic Radiology